Mosques as monuments: an inter-Asian perspective on monumentality and religious landscapes. (January 2018) - Koch, Natalie; Valiyev, Anar; Hazmi Zaini, Khairul
This article examines monumental mosques and particularly those that are built to be and function more as monuments than as places for worship. We consider the role of monumentality in religious landscapes by way of six exemplary mosques in three different world regions – Central Asia, the Arabian Peninsula, and Southeast Asia. Tracing their unique histories and the identity narratives inscribed in their built form, we stress three broader commonalities among these mosques-as-monuments: (1) each is the result of top-down, state-funded planning infused with strong nationalist or ideological symbolism, (2) each was designed to be an iconic architectural showpiece in the country's capital city, and (3) each represents a stark contrast to other places of worship within that national or regional context. In this unique comparative study, we use an interpretive approach designed to push the research on monuments and monumentality into new directions and new empirical contexts, and specifically to ask why and with what effect some religious sites are primarily monuments and only secondarily places of worship.